Social support and psychological distress in patients with gastrointestinal cancer: A structural equation model - Angulo-Salas, Roger Joaquín (2025)
The aim of this study was to analyse how different dimensions of social support predict psychologicaldistress, understood as anxiety and depression, in patients with gastrointestinal cancer. A total of 353adult patients participated, most of whom were women (70.8%), diagnosed in the outpatient clinic of theabdominal surgery department. An explanatory, non-experimental, cross-sectional design was used. Theinstruments used were the Perceived Social Support Questionnaire (MOS) and the Hospital Anxiety andDepression Scale (HADS).The internal structure of the scales was previously evaluated using confirmatory factor analysis, andreliability was verified with alpha and omega coefficients. Subsequently, a structural equation model(SEM) was used in R Studio 4.4.3 software, which showed a good fit (χ²/gl = 2.30; CFI = .995; RMSEA = .057). The results indicated that emotional support (β = −.23), positive interaction (β = −.32) and affective support (β = −.20) were associated with a decrease in psychological distress, while tangible support (β = .34) was associated with an increase in psychological distress. In conclusion, the impact of social support varies depending on its type, as while some forms such as emotional support or positive interaction act as protective factors, others such as tangible support could generate adverse effects by promoting dependence or stress. Therefore, it is suggested that psycho-oncological interventions prioritise the strengthening ofemotional bonds and carefully monitor the way in which practical support is provided.